The Effectiveness of the Scaffolding Method to Improve Teacher Literacy Competence in Compiling Teaching Materials Based on Pancasila Student Profiles - Puspitasari, Ade Putri; Aryanto, Sani (Universitas Teuku Umar, 2024)
The purpose of this research is to provide an overview of the process of improving teacher competence in compiling teaching materials based on Pancasila student profiles in Elementary Schools. This study uses a quasi-experimental method of one group pre-test post-test design which includes 3 steps, namely: pre-test, treatment, and post-test by utilizing the implementation of the scaffolding program as a treatment to be carried out. The scaffolding program in this study has 3 stages, namely; (1) Modeling, (2) Provision of Materials and (3) Final Stage. This study was conducted on 31 teachers from levels I-IV at SDN Harapan Baru III, Bekasi City, located at Jl. Raya Perjuangan No. 48, RT.002 / RW.003, Harapan Baru, Kec. Bekasi Utara, Bekasi City, West Java 17123. The rationale for selecting this school is based on the condition of teacher literacy competence in compiling teaching materials that need to be improved. The results of this study are seen based on a comparison of the average results of the pre-test and post-test which obtained a sig value of 0.000 and less than 0.05 which proves that this study is considered successful in improving teacher literacy competency so that it can make it easier for teachers to prepare appropriate teaching materials, of course teaching materials based on the Pancasila Student Profile.